Bilingualism in Early Education: A Case Study at Sekolah Alam Cempaka Kids - Putra, Eka Dwi (PT. Publikasiku Academic Solution, 2025)
This study investigates the implementation of bilingualism in early education at Sekolah Alam Cempaka Kids, focusing on the forms of bilingualism, dominant language use, and influencing factors. Bilingualism, crucial for global communication, is increasingly integrated into education to enhance students' linguistic and cognitive skills. However, challenges such as limited teacher proficiency and inadequate resources hinder its effectiveness. The research aims to analyze bilingual practices, identify the dominant language, and explore factors affecting its application. Using a descriptive qualitative approach, data were collected through observations, interviews with teachers, and document analysis. Participants included five teachers and 25 students aged 4–6 years. Findings revealed that code-switching and code-mixing were prevalent, with Indonesian as the dominant language and English used sparingly. Key influencing factors included teachers' limited English proficiency, insufficient resources, and minimal parental support for English use at home. The study highlights the need for structured bilingual programs, enhanced teacher training, and improved resources to optimize bilingual education. These findings contribute to understanding bilingualism in early education settings, particularly in Indonesia, and offer practical recommendations for educators and policymakers to foster effective bilingual learning environments.